2007
DOI: 10.1111/j.1533-2500.2007.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Spinal Cord Stimulation in a Patient With Severe Cerebral Ischemia and Upper Extremity Ischemic Pain

Abstract: Spinal cord stimulation (SCS) is used in the treatment of chronic pain, ischemia because of obstructive arterial disease, and anginal pain. Recently, a number of studies have described the effects of the high cervical SCS, including increased cerebral blood flow, although the underlying mechanisms are unknown. This case report describes a patient with a severe complex ischemic condition affecting both cerebral and upper limb blood flow with an associated complex regional pain syndrome in upper limb. While all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Only in five cases the SCS was implanted in patients previously revascularised, presenting a much compromised distal arterial bed and one SCS was positioned in the cervical peridural space for the treatment of steal syndrome in a haemodialysis patient. Application of SCS in the cervical space has been previously reported in literature for the treatment of different diseases . Results of our study were very encouraging: group A showed a healing rate of 100%, group B of 78%, group C of 57% and group D of 88%.…”
Section: Discussionsupporting
confidence: 63%
“…Only in five cases the SCS was implanted in patients previously revascularised, presenting a much compromised distal arterial bed and one SCS was positioned in the cervical peridural space for the treatment of steal syndrome in a haemodialysis patient. Application of SCS in the cervical space has been previously reported in literature for the treatment of different diseases . Results of our study were very encouraging: group A showed a healing rate of 100%, group B of 78%, group C of 57% and group D of 88%.…”
Section: Discussionsupporting
confidence: 63%
“…According to the previous experiences of Mazzone et al [19,20] , the evidence of redistribution of CBF rather than a clear increase was shown in such patients. More recently, De Andrés et al [53] published a case harboring both severe cerebral ischemia and upper extremity ischemic pain, successfully treated with cervical SCS. A large series has recently been published by Liu et al [54] who observed an increase of cerebral blood perfusion and catecholamine in CSF after SCS, suggesting that SCS increases cerebral blood perfusion, attenuates oxidative stress and increases biogenic amines in comatose patients.…”
Section: Clinical Trials On Hypoperfusion Syndromes In Humansmentioning
confidence: 99%
“…However, there is not yet an ultimate scientific explanation; moreover, a clear understanding of the mechanisms elicited by SCS is still lacking [4,53,68]. Different hypotheses have been reported in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
“…SCS has been shown to augment CBF and speculated to protect the brain from focal ischemia in a large series of experiments, both on animals and on humans [47,48,49,50,51,52,53], and has been proposed for the treatment of several cerebral low-perfusion syndromes [54,55,56,57,58,59,60,61,62,63,64,65,66,67]. However, there is not yet an ultimate scientific explanation; moreover, a clear understanding of the mechanisms elicited by SCS is still lacking [4,53,68].…”
Section: Discussionmentioning
confidence: 99%